Contemporary mobility of herders in central Mongolia - Jargalsaikhan, Azjargal, author; Batjav, Batbuyan, author; Baival, Batkhishig, author; Ulambayar, Tungalag, author; Lhagvasuren, Tamir, author; Tsogtbaatar, Solongoo, author; Nutag Action and Research Institute, publisher (Colorado State University. Libraries, 2015)
Social-ecological changes occurring in recent years have complicated herders' migration patterns, and because of rangeland climate variability, nomadic movement patterns have changed. The aim of this study was to determine how the present movement patterns of herders situated in different steppe regions along the road infrastructure corridor of central Mongolia have been affected by the intensification of community-based natural resource management activities and household livelihood levels, and to identify how herders adapt to those changes in their movement practices. The number and distance of herders' movements increased between 2010 and 2011, depending on regional geographical location and community-based natural resource management activities. In particular, household income and the number of livestock herders owned determined how far they moved. In the period 2010-2011 in central Mongolia there was a trend of movement from the western aimags to the forest steppe and from the desert steppe to the steppe and forest steppe, across administrative borders. Herders have a variety of ways to cope with social-ecological change which demonstrates the basic need for developing location-specific policies when establishing movement regulations and implementing risk reduction measures.
Presented at the Building resilience of Mongolian rangelands: a trans-disciplinary research conference held on June 9-10, 2015 in Ulaanbaatar, Mongolia.
Keywords: Mongolia; movement patterns; regional geographic location; herders; CBRM; movement across the administrative borders